2018
DOI: 10.4236/ojmip.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Pregnant Women from a West-African Population

Abstract: Thyroid dysfunction is frequent in pregnant women and is often associated with an increased risk of adverse maternal and fetal outcome. In the present work, thyroid function of pregnant women from Benin republic was studied. Two hundred forty (240) pregnant women, without thyroid disease history, have been included in the study. A blood sample was drawn for measurement of TSH, free T3 and free T4 serum levels. From the first to the third trimester, plasma levels of free T3 and free T4 decreased when plasma lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…19 In the current study, we had found that there was no statistically significant relationship between development of thyroid disorders and age of women, nor gravidity status nor the trimester. This comes in contrary with Awede et al, 15 who observed positive relationship between hypothyroidism with age, trimester and number of gravidity. This may be due to the difference in the sample size, population characteristics.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…19 In the current study, we had found that there was no statistically significant relationship between development of thyroid disorders and age of women, nor gravidity status nor the trimester. This comes in contrary with Awede et al, 15 who observed positive relationship between hypothyroidism with age, trimester and number of gravidity. This may be due to the difference in the sample size, population characteristics.…”
Section: Discussioncontrasting
confidence: 66%
“…Another study in Africa comparing the prevalence of thyroid functions in pregnancy using 2011ATA guidelines and 2017 ATA guidelines. In a study by Awede et al, 15 Two hundred and forty (240) pregnant women were included in the study. It showed that Thyroid dysfunction was present in 24.17% of the pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, thyroid disorders were present in 14.58% of pregnant women. The frequency of subclinical hypothyroidism, overt hypothyroidism, hypothyroxinemia and hyperthyroidism were respectively 9.58%, 0.42%, 2.91% and 1.67% [15] . In this study, similar comparison was done and revealed that the prevalence of thyroid dysfunction according to 2011 ATA reference ranges was 49% (39% SCH, 6% OH, 4% isolated hypothyroxinemia), while according to 2017 ATA reference ranges was 23% (13% SCH, 3% OH and 7% isolated hypothyroxinemia).…”
Section: Discussionmentioning
confidence: 94%
“…This comes in contrary with Awede et al who observed positive relationship between hypothyroidism with age, trimester and number of gravidity. This may be due to the difference in the sample size, population characteristics [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Aboelroose AA reported overall incidence of thyroid disorders in low risk pregnant women was 49 % and 23 % as per 2011 ATA guidelines and 2017 ATA guidelines respectively [9]. Whereas, Awede B et al conducted study over 240 pregnant women and found thyroid dysfunction was present in 24.17 % and 14.58 % according to 2011 ATA guidelines and 2017 ATA guidelines respectively [10]. Wang W et al in a multicenter cohort study among 2899 pregnant women in China, who did not use trimester specific reference ranges as recommended by ATA found prevalence of thyroid dysfunction of 10.2 % [11].…”
Section: Discussionmentioning
confidence: 99%